An emerging technique of medicated chewing gum in drug delivery system: a review - Khatiwara, Deepika; Ranabhat, Priyanka; Paul, Moumita; Bagchi, Arnab (Journal of Applied Pharmaceutical Research, 2021)
Many advances in research and technology have been made in the oral route of drug delivery system in recent years. Because of increased patient compliance not only in geriatric and paediatric patients, but also in the general population, the oral channel of drug delivery system- medicated chewing gum has received worldwide recognition throughout the year. Chewing gum can be used as a mobile medication delivery device for both local and systemic drug administration via the oral route. Because of its ease and ability to be administered without water, it is an exceptional drug delivery device for self-medication. The production technique, advantages, disadvantages, factors impacting the release of medicament, assessment parameter, difficulty related with chewing gum manufacture, and future trends have all been examined in this review paper